Coniochaeta mutabilis keratitis with an unusual mode of transmission treated with penetrating keratoplasty and systemic antifungals - Victor F. Bellanda; Craig W. See (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To report a case of fungal keratitis caused by Coniochaeta mutabilis along with its treatment and discuss the possibility of an unusual mode of transmission. Only a few cases of ocular C. mutabilis infection have been reported, and this is the first presenting domestic fowl as a potential source of infection. Observations: A 52-year-old woman presented with a corneal ulcer following a week of increasing eye pain. Five months prior, she had a corneal abrasion in the same eye that resulted from trauma during yard work. Two weeks before presentation, she cared for a chicken with ocular infection. Culture of the corneal scraping identified Coniochaeta mutabilis, a rarely described fungal pathogen. After multiple treatment modalities were attempted, the patient ultimately underwent penetrating keratoplasty. No signs of infection recurrence were present during follow-up after the procedure. Conclusions and Importance: C. mutabilis keratitis is a rare condition that typically presents with an aggressive nature and requires multiple forms of treatment. Here, we report direct contact with an infected chicken cornea as a possible mode through which the disease was acquired. Early suspicion of fungal etiology in cases of keratitis allows directed treatment, which may improve visual outcomes. Acknowledging unusual modes of transmission may help bring this differential diagnosis into consideration. Furthermore, given the scarcity of literature about this disease, individual case reports are informative for guiding future treatment and research.